Characterization of Effective Native Lactic Acid Bacteria as Potential Oral Probiotics on Growth Inhibition of Streptococcus mutans - Golshahi, Maryam; Pirnia, Mohammad Mehdi; Jafari, Parvaneh; Ebrahimi, Elahe; Tafvizi, Farzaneh; Dameshghian, Mahsa; Tajabadi Ebrahimi, Maryam (Applied Food Biotechnology, 2021)
Background and Objective: Probiotics' effects on harmful oral bacteria have been verifed. As antibiotic resistance becomes a major problem, searching for novel potential species is important. The objective of this study was to select novel safe strains of lactic acid bacteria with potentials as oral probiotics. Furthermore, ability of these strains to suppress growth and attachment of Streptococcus mutans as the most important cariogenic bacteria in tooth decay was investigated. Material and Methods: Initial identification tests, including Gram staining and catalase and oxidase tests, were carried out on 22 strains of lactic acid bacteria isolated from Iranian traditional dairy products. Safety of the strains was assessed using hemolysis test and antibiotic resistance assessment. Strains were then assessed for probiotic characteristics such inhibition of Streptococcus mutans growth, tolerance to lysozyme enzymes and ability of adhesion as well as ability of decreasing Streptococcus mutans adhesion. Selected strains were identified using16S rRNA molecular method. Results and Conclusion: Of all strains, four strains with the optimal probiotic characteristics were selected. These included one Lactobacillus brevis, one Lactobacillus casei and two Lactobacillus paraceasei. These four strains showed strong antimicrobial characteristics against Streptococcus mutans, were resistant to oral lysozyme enzymes and included high adhesion abilities to polystyrene wells. Furthermore, they decreased Streptococcus mutans attachment; thus, biofilm formation by this bacterium was prevented. These strains were recognized as safe strains since they were approved in assessments of antibiotic susceptibility and hemolytic activity. Therefore, these four strains are suggested as oral probiotics. Conflict of interest: The authors declare no conflict of interest.